PENINGKATAN KREATIFITAS DAN KEMAMPUAN KOGNITIF SISWA MELALUI OUTDOOR LEARNING ACTIVITY - Wibowo, Yuni (MAJALAH ILMIAH PEMBELAJARAN, 2012)
The aims of this research is improvements studets ceativity and cognitive achievments through outdoor learning activity at the SMPN 2 Bambanglipuro Bantul. This research is a classroom action research with kemmis and Taggart Model. The stage are planning, acting and observing, reflecting. The research had done in 2 cyclic with topics ingenhouz and sachz experiments. Subject of this research were 30 students in grade VII E. The instruments were teaching guide, worksheet, instructional media, creativity observation sheet, and test of cognitive. Data of instructional process and students creativity were analized by descriptive analysis. Data of students cognitive was analyzed by gain score. The results showed that students creativity increased. It have three category of students creativity were poor, fair, and good. In cyclic I, category of poor was 42,38%, fair was 45,17% and good 11,9%. In cyclic II, category of poor was 27,14%, fair was 43,33%, good was 29,53%. The students cognitive has increased from 54,67 in pracyclic, 80,67 in cyclic I, and 96,67 in cyclic II with fair in gain score.